(untitled) (Marketing Journal, 2025)
The article examines the theoretical foundations of restaurant business development in the global environment and analyzes the external and internal factors affecting restaurant operations using various methods. In the context of globalization and increasi ng international competition, the development of national restaurant enterprises gains particular importance. The study focuses on analyzing the prospects for the Uzbek national restaurant “Chorlar,” located in the “Milliy Bog” park in Tashkent, to enter t he international market within the framework of global marketing concepts.